Reward And Punishment Dalam Pendidikan Disiplin Shalat Lima Waktu Anak Pegawai Negeri Sipil - Abdi, Zainul; Majdi, Muhammad (STAI AL FALAH Banjarbaru, 2022)
This study aims to analyze the education of five daily prayers with the reward and punishment method for civil servant children, due to the tight work schedule that will affect interactions with children. So education for the five daily prayers with the reward and punishment method will show the efficiency of activities with the results obtained to keep paying attention to the problem of praying five times for their children. Data collection techniques used in this study were documentation, interviews, and observation. The subjects in this study were parents who worked as civil servants who had children and carried out prayer discipline education for children. While the object of this research is the discipline of five daily prayers with the reward and punishment method for the children of civil servants who were analyzed descriptively and qualitatively. The results of the study on the discipline of praying five times with the reward and punishment method for children of civil servants. The implementation of disciplined education with the reward method from the MF family is 1) verbal, 2) nonverbal, 3) buying what you like. Families D and A are also the same 1) giving rewards, 2) verbally. Meanwhile, the implementation of disciplined education using the punishment method from the MF family did not carry out the punishment because the child obeyed. Families D and A have applied the punishment stage, namely physical punishment (pinch).Keywords: Rewards for Punishment children, Prayer Discipline Education, PNS children.